Economic growth and development - La Grandville, Olivier de (Frontiers of economics and globalization ;, 2011)
Since the very beginnings of economics as a science, which might be dated from Ibn Khalduns Introduction to History (1377), the challenge of making societies escape from poverty and attain some degree of prosperity has always been, and will remain, a fundamental issue. It was and it is still recognized today that this central venture is multi-faceted. Inasmuch as investment and technical progress are central in the growth and development process, many other dimensions must be taken into consideration, such as institutions, the openness of the economy, the protection of the environment. This book will presents cutting edge research on each of these issues and is features a preface from Ken Arrow.